Development of an optical tyrosinase biosensor (TCA) for detection of "Parathion-Methyl". Issue 4 (15th July 2019) - Polatoğlu, İlker; Cakıcıoglu Ozkan, Fehime
Abstract : Purpose: This paper aims to present a novel and cost-effective optical biosensor design by simple preparation method for detection of "parathion-methyl, " which is a model pesticide pose to public health and the environment. Design/methodology/approach: The optical enzyme biosensor (TCA) for detection of pesticide "parathion-methyl" was developed on the basis of immobilization of tyrosinase enzyme on chitosan film by adsorption technique. The analytic performance of TCA was investigated by measuring its activity with Ultraviolet (UV) visible spectrophotometer. Findings: Uniform porous network structure and protonated groups of chitosan film provided a microenvironment for tyrosinase immobilization evident from Fourier transform infrared (FTIR) spectroscopy and Atomic Force Microscopy analysis. TCA has a wide linear detection range (0-1.03 µM) with high correlation coefficient and it can detect the parathion-methyl concentration as low as 159 nM by noncompetitive inhibition kinetics. Using the TCA sensor both for ten times and at least 45 days without a significant loss in its activity are the indicators of its good operational and storage stability. Moreover, TCA can be applicable to tap water, providing a promising tool for pesticides detection. Originality/value: This is the first time to use the in situ analytical technique that can improve the performance of optical enzyme sensor provided to control the pesticide residue better with respect to traditional techniques. The effect of organic solvents on the performance of optical enzyme biosensor was investigated. Inhibition kinetic of the solvents rarely encountered in literature was also studied besides the pH and temperature tolerance of the optical biosensor.